Coffee and carbon offsets for smallholders: can carbon financing promote cleaner coffee in Nicaragua? - Porras, Ina; Amrein, Alexandra; Vorley, Bill (2015)
This report looks at the ongoing PASCAFEN-CamBio2 project (Sustainable Agriculture in Coffee Plantations in Nicaragua) to understand the potential of carbon-offset funding for smallholder agriculture in coffee-producing landscapes. Carbon emission reductions in the project are expected over the course of 20 years via the establishment and maintenance of aerial biomass (trees in the coffee agroforestry system), soil carbon biomass from composting, and avoided emissions from nitrogen reductions. The project is expected to produce higher coffee yields, better disease control, improved coffee quality and a reduction in defective coffee beans, and important socio-economic benefits by improving income and livelihoods and strengthening farmer organisations. Business benefits along the value chain will be enhanced by improving environmental resilience at the production end of the value chain, and instruments like insetting (offsetting within existing value chains) can provide important funding to ensure long-term stability. The project is based on the principle that small-scale farmers deliver important services to the environment through projects like organic agriculture, and that upscaling these actions can have major significance for national climate change strategies.